CAPACITY BUILDING AGEN PEMULIHAN INTERVENSI BERBASIS MASYARAKAT (IBM) DALAM PENANGGULANGAN PENYALAHGUNAAN NAPZA - Lessy, Soraya; Indrakentjana, Bambang; Ismudiyati, Yuti Sri (Jurnal Ilmiah Kebijakan dan Pelayanan Pekerjaan Sosial (Biyan), 2024)
The increasing abuse of Narcotic Drugs and Psychotropic Substances (NDPS) in Jayagiri Village, Cianjur Regency, represents a significant issue that necessitates comprehensive intervention from the government and community elements. In addressing the issue of NDPS abuse in Jayagiri Village, in 2022, the National Narcotics Agency (BNN) of Cianjur Regency, in collaboration with the village government, established a Community-Based Intervention (IBM) in Jayagiri Village as part of the Desa Bersinar program. Community participation is crucial in efforts to combat NDPS abuse. Therefore, the IBM recovery agent was established. Following its formation, this recovery agent received capacity-building to enhance knowledge and skills in implementing IBM activities/services. This study aims to develop technology engineering for capacity building and support for IBM recovery agents, focusing on the primary concept of assisting IBM recovery agents in implementing activities/services in the field, as well as community participation in program evaluation. This study employs a qualitative approach using the Participatory Action Research (PAR) method. Data collection involves documentation studies, observations, interviews, and Focus Group Discussions (FGD). Additionally, two tools or methods supporting FGD are utilized: Methodology Participatory Assessment (MPA) and Technology of Participation (ToP). The results indicated that the design of capacity building and mentoring for IBM recovery agents effectively enhanced their knowledge and skills. Furthermore, community participation in providing input or feedback on IBM activities/services was effective for the future development of the IBM program. The achieved outcome was that the implementation of IBM activities and services became more optimal and of higher quality.